2021
DOI: 10.29312/remexca.v12i2.2687
|View full text |Cite
|
Sign up to set email alerts
|

Biosorción y tolerancia de Pb, Cr y Cd por la biomasa de Pleurotus ostreatus (Jacq. Ex Fr.) P. Kumm

Abstract: A nivel mundial, el uso indiscriminado de productos metálicos vertidos en agua utilizada en la agricultura ha generado una grave contaminación, por lo tanto, es importante establecer una metodología para su descontaminación a través de procesos biológicos, con hongos basidiomicetos ya que se ha demostrado que pueden degradar una serie de contaminantes orgánicos persistentes utilizando enzimas extracelulares, además de eliminar metales disueltos del agua mediante biosorción, actuando, como un intercambiador nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
2
2
0
1
Order By: Relevance
“…Wu et al (2016) reported that Pleurotus eryngii removed up to 92.17% of Mn from aqueous solutions after 15 days of incubation, supporting the ndings of the present study Aguilar et al (2021). assessed the capability of Pleurotus ostreatus to remove metals from aqueous solutions, nding the highest removal e ciencies for Pb (75%), followed by Cr (42%) and Cd (2.25%).…”
supporting
confidence: 87%
“…Wu et al (2016) reported that Pleurotus eryngii removed up to 92.17% of Mn from aqueous solutions after 15 days of incubation, supporting the ndings of the present study Aguilar et al (2021). assessed the capability of Pleurotus ostreatus to remove metals from aqueous solutions, nding the highest removal e ciencies for Pb (75%), followed by Cr (42%) and Cd (2.25%).…”
supporting
confidence: 87%
“…The images show homogeneous sorption of Pb­(II) ions (Figure d) and a few particulates (inset in Figure b) distributed along the hyphae, which are in correspondence with the available functional groups (Figure e,f). Similar studies on the sorption of heavy metals, such as Zn–Pb­(II) (deposited on root epiderma) and chromium (deposited on live mycelium), showed the formation of particulate-like heavy metal crystals. This indicates the ability of dry hyphae, similar to live networks, to adsorb metal ions leaching from salt solutions and precipitate at the hyphal surface.…”
Section: Resultssupporting
confidence: 55%
“…On the other hand, the highest metal adsorption was observed at a pH of 1.0 with the analyzed biomass (Fig. 2), which is similar to that reported for P. sajor-cajor, G. lucidum and A. bitorquis, with an optimal pH of 2.0 and 2.5 for the elimination of Iron (III), Nickel and Cobalt [45], but some authors report different pH values optimal for the removal of this and other metals, such as A. bisporus biomass, in which the maximum removal efficiencies were 79.82%, and 67.30% at pH 7.5 and pH 5.5 for Cadmium (II) and Zinc (II), respectively [39], for the biosorption of Cadmium, Lead, and Copper by organic carbon of A. bisporus and P. ostreatus, it was observed that an increase in pH increased the adsorption capacity [18], a pH of 5.0 for the biosorption of different heavy metals by peach pod modified and colonized by A. blazei [41], different pH values (3.5, 4.5, 6.0 and 6.5), for H. tawa [42], a pH of 8.0 for A. campestris used as a biosorbent in the treatment of wastewater containing Copper and Lead ions in a dynamic process [43], an initial pH of 6.0 for the biosorption of cupric ions for a chitosan compound from A. bisporus [44], and for different mushrooms [45], a pH between 5.0 and 7.0 for removal of Chromium, Copper, Lead and Mercury by different macromycetes [22,24,45] and [48]. This is probably since the dominant species (CrO4 2and Cr2O7 2of Cr ions in solution, interact more strongly with the ligands carrying positive charges [47,49].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is very important to try to eliminate the greatest number of pollutants from the different contaminated ecological niches to reduce said contamination and reduce the risks to human health. The elimination of different heavy metals and other contaminants by this type of fungi has been reported, such as: The biosorption of Cadmium, Lead and Copper by organic carbon of A. bisporus and Pleurotus ostreatus [18,19], the accumulation of Mercury, Cadmium, Lead and Arsenic by Amanita ponderosa, Boletus edulis, Marasmius oreades and Tricholoma georgii [20], the accumulation of different heavy metals by the edible fungi Melanoleuca cognata and Melanoleuca stridula [21], the removal of Copper (II) by different macromycetes [22], the removal of Cu (II), Zn (II) and Cd (II) by a mineral-rich compound of A. bisporus [23], the removal of Mercury, Lead, Cadmium and Chromium by P. ostreatus [24], the removal of Lead and Cadmium in water by biochar from Ganoderma lucidum [25], the phytoremediation of soils contaminated with heavy metals by P. ostreatus and Megathyrsus maximus [26], and the removal of heavy metals from coal wash effluents with the fungus P. ostreatus [27]. On the other hand, the adsorption efficiency of other pollutants such as: paracetamol and α-ethynyl estradiol (EE2) by A. bisporus and Lentinula edodes has also been reported [28], the removal of sulfonamides by P. ostreatus [29], acid red 97 and crystal violet by A. bisporus [30], malachite green by different macromycetes [31], and textile dyes using Trametes versicolor, P. ostreatus and A. bisporus [32].…”
Section: Introductionmentioning
confidence: 99%